2006
DOI: 10.5507/bp.2006.006
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effect of fluoridated milk in a bacterial biofilm - Enamel model

Abstract: Objectives:The purpose of this study was to investigate the effect of milk and fluoridated milk on bacterially induced caries-like lesions. Sample and methods: Extracted impacted human molars were cut in half and covered with a varnish leaving a 4×4 mm window. The samples were coated with biofilm of S. sobrinus and were further divided into three experimental groups of S. sobrinus, S. sobrinus and milk and S. sobrinus and fluoridated milk. As negative controls served teeth incubated in saline. Of twenty tooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The role of milk is very complex, on one hand it can act as a fluoride carrier thus preventing lesion progression; conversely milk itself contributes to maturation of the bio-film resulting in a higher de-mineralizing potential and greater volume of lesions. 23 The profiles of mineral content showed that all the test groups gained mineral as a result of pH cycling with fluoridated milk. Mineral was lost when plain milk and deionized water were used as the treatment medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of milk is very complex, on one hand it can act as a fluoride carrier thus preventing lesion progression; conversely milk itself contributes to maturation of the bio-film resulting in a higher de-mineralizing potential and greater volume of lesions. 23 The profiles of mineral content showed that all the test groups gained mineral as a result of pH cycling with fluoridated milk. Mineral was lost when plain milk and deionized water were used as the treatment medium.…”
Section: Discussionmentioning
confidence: 99%
“…22 Though a number of in vitro studies have demonstrated the re-mineralizing efficacy of different concentrations of fluoridated milk, the re-mineralization effect of increasing the volume of fluoridated milk within the same concentration is still unclear. [23][24][25][26][27][28][29] Thus the objectives of this study were to investigate whether increasing (1) the concentration of fluoride in milk and (2) the volume of fluoridated milk alters its re-mineralizing efficacy. The null hypothesis tested was that increasing the fluoride concentration and volume of fluoridated milk would increase its remineralization efficacy on initial enamel carious lesions.…”
Section: Re-mineralizationmentioning
confidence: 99%
“…In this study, fluoridated milk is used as a vehicle as it is easily accessible and also rich in calcium which could further enhance remineralization. The effectiveness of fluoridated milk on enamel remineralization has shown positive effect on caries reduction,[ 22 23 24 ] whereas only few studies have determined the effect of fluoridated milk on root dentine remineralization. [ 8 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Milk as a common nutrient seems to play a complex role in in-vitro biofilm--enamel interactions stimulating bacterial demineralization on one hand, and, as effective fluoride carrier, inhibits caries-like demineralization (Arnold et al, 2006). It was possible to verify an inhibition of enamel lesion formation by fluoridated milk already after 40 h of acid exposure and before any clearly visible clinical signs of demineralization were seen (Engström et al).…”
Section: Introductionmentioning
confidence: 87%